2015
DOI: 10.3171/2014.12.spine13994
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral versus unilateral interlaminar approach for bilateral decompression in patients with single-level degenerative lumbar spinal stenosis: a multicenter retrospective study of 175 patients on postoperative pain, functional disability, and patient satisfaction

Abstract: OBJECT The bilateral and unilateral interlaminar techniques for bilateral decompression both demonstrate good results for the treatment of degenerative lumbar spinal stenosis (DLSS). Although there is some discussion about which approach is more effective, studies that directly compare these two popular techniques are rare. To address this shortcoming, this study compares postoperative functional disability, pain, and patient satisfaction among patients with single-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
0
20
0
1
Order By: Relevance
“…Although several studies showed good results for bilateral decompression via unilateral approach [1,4] it is still unclear which technique is the best for decompression of spinal stenosis [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies showed good results for bilateral decompression via unilateral approach [1,4] it is still unclear which technique is the best for decompression of spinal stenosis [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…This requires careful evaluation of current best practice and new surgical techniques in order to provide the best available care for these patients to reduce pain and disability, and to improve mobility. Several studies have shown good outcomes for a ULBD approach for the management of LSS; however, it is not clear whether this approach is superior, as high quality evidence is lacking in the literature. That said, these studies do provide evidence suggesting that the ULBD may be associated with better outcomes than with traditional laminectomy, and reduce hospital stay and the overall cost of the intervention (REF).…”
Section: Discussionmentioning
confidence: 99%
“…Den Boogert et al retrospectively compared postoperative functional disability, pain, and patient satisfaction among 175 patients with LSS who underwent either a ULBD or a traditional laminectomy. Patients in the ULBD group reported better overall satisfaction with the procedure and a reduction in visual analogue score (VAS) leg symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…After the first laminotomy is performed on one side, the deep cortical surface of the contralateral lamina is undercut, and drilling is extended to the contralateral lateral recess, permitting the removal of the ligamentum flavum. It has been reported the usefulness of both procedures to treat patients with single level spinal stenosis [11]. In a recent prospective study, in patients with multilevel decompression, UBLD was found superior to MILD in term of low back pain and lumbar function (increased sagittal translation and lumbar lordosis in MILD compared to UBLD, probably due to the removal of half of the spinous processes in the MILD) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Minimal invasive procedures such as the muscle-preserving interlaminar decompression (MILD) [8] and the unilateral approach for bilateral decompression (ULBD) [9] have been reported in the literature [10]- [12] as alternative techniques for lumbar spinal stenosis decompression. These techniques are both efficacious to treat patients with single level spinal stenosis [11]. Moreover, in a recent randomized trial [12] and in a recent systematic review [13], it has been evidenced that ULBD is as effective as open laminectomy in improving clinical functional outcome, with the additional benefits of a significantly greater decrease in pain, postoperative recovery time, time to mobilization and opioid use.…”
Section: Introductionmentioning
confidence: 99%